Protein intake: Effect of timing - Hoffman, J. R. (Strength and Conditioning Journal, 2007)
Differences in protein requirements for athletes and nonathletes, and different types of athletes (i.e., endurance vs.strength/power) are well acknowledged. This has led many athletes to use protein supplements as a means of achieving required protein intakes. Recent research has begun to examine the importance of protein timing. Specifically, does it make a difference when the protein is ingested in regards to augmenting the acute physiological response to a training session or in enhancing recovery from exercise. This review focuses on the timing of protein intake and its effects on skeletal muscle remodeling.